2018
DOI: 10.1093/jn/nxx070
|View full text |Cite|
|
Sign up to set email alerts
|

Progressive Increases in Dietary Iron Are Associated with the Emergence of Pathologic Disturbances of Copper Homeostasis in Growing Rats

Abstract: Increasing dietary iron intakes to ∼9.5-fold above dietary recommendations caused copper deficiency. Importantly, human iron supplementation is common, and recommended intakes for at-risk individuals may be ≤10-fold above the RDA. Whether these iron intakes perturb copper metabolism is worth considering, especially since copper defi-ciency can impair iron utilization (e.g., by decreasing the ferroxidase activity of ceruloplasmin).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Therefore, we only reported the results of multiple regression analyses showing significant results. Further, it is known both Cu and iron have similar binding proteins in cerebral tissue and they affect each other during uptake (Fox 2003;Ha et al 2018); therefore, the iron level might affect the present results. To exclude such possibilities, we additionally performed non-whole brain multiple regression analyses including hair iron level as an additional covariate.…”
Section: Statistical Analyses Of Non-whole Brain Analysesmentioning
confidence: 90%
“…Therefore, we only reported the results of multiple regression analyses showing significant results. Further, it is known both Cu and iron have similar binding proteins in cerebral tissue and they affect each other during uptake (Fox 2003;Ha et al 2018); therefore, the iron level might affect the present results. To exclude such possibilities, we additionally performed non-whole brain multiple regression analyses including hair iron level as an additional covariate.…”
Section: Statistical Analyses Of Non-whole Brain Analysesmentioning
confidence: 90%
“…Hb and Hct in whole blood were measured by standard methods. 53 , 54 Serum ferritin concentration was quantified with the Mouse Ferritin ELISA Kit (ab157713; Abcam). Plasma EPO concentration was measured by Mouse Erythropoietin Quantikine ELISA Kit (MEP00B; R&D Systems).…”
Section: Methodsmentioning
confidence: 99%
“… 54 , 55 TIBC was assessed as previously described. 53 , 54 TSAT was calculated as serum iron/TIBC × 100. Non-heme iron content in tissues was determined using a standard acid digestion, chromogen-based colorimetric assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm a significant influence of Cu on the release of tissue Fe. Ha et al [322] showed that Cu metabolism is impaired when dietary Fe intake is >10 times higher than the normal Fe supply established by WHO. Significantly elevated levels of Fe may result in anemia, likely due to a lack of Cu in the diet [323].…”
Section: Fe Vs Cumentioning
confidence: 99%